Les débuts d'une revue néo-salafiste : Muhibb al-Dîn al-Khatîb et Al-Fath de 1926 à 1928 - Catherine Mayeur-Jaouen (Revue des Mondes Musulmans et de la Méditerranée)
Al-Fath, the Egyptian reformist weekly, was established in 1926 in Cairo and it appeared regularly until just after the Second World War. This journal was established by Muhibb al-Dîn al-Khatîb (1886-1969), a Syrian who lived in Cairo. Al-Fath is above all a religious journal whose aim is to defend Islam on all fronts : it is presented as an Islamic, scientific and moral journal whose mission is to fill the gap in the Egyptian press, monopolised by the liberal press published by Syrians living in Cairo. The journal meticulously lists all the signs of crisis in the threatened Islamic world : worry in face of increasing Westernisation in the Orient (tafarnuj), anguish and the scandalous feelings in relation to the secular reforms of Kemalist Turkey, worry about the proselyte presence of Christian missionaries in the Orient and the increasing atheism and positivism among Muslims. As for the feminine question, al-Fath is strongly against unveiling for women. In the assailed world depicted by al-Fath, the journal however signals a few rays of hope : the creation of Saudi Arabia as well as the creation of clubs and Islamic associations among which are the Muslim Youth and the Muslim Brotherhood which Khatîb supports.